Utility of Cardiac Troponin I as a Marker of Severity in Non-Ischaemic Heart Failure - Udosen, A; Ansa, V O; Umoh, I O; Shogade, T; Effiong, B; Akpu, B; Epoke, E; Udoh, E (West African journal of medicine, 2025)
Biomarkers are crucial for assessing the severity of heart failure (HF) and monitoring its treatment. Cardiac troponin I (cTnI) has traditionally been used as a marker for myocardial injury but its role in non-ischemic heart failure (NIHF) remains unclear. This study was aimed at determining the relationship between cTnI and left ventricular function and geometry in NIHF patients. This was a cross-sectional comparative study that recruited 60 NIHF patients and 60 controls from the cardiology unit in a tertiary hospital. All participants had cTnI assay and transthoracic echocardiography done to assess left ventricular function and geometry. Data was analysed using Statistical Package for Social Sciences (SPSS) version 23. The level of statistical significance was fixed at p value < 0.05. The mean age of patients with NIHF was 50.0±12.6 years versus 50.3±12.0 years for controls (p=0.456). The mean serum cTnI level was 358.52±56.60ng/L in NIHF patients versus 218.54±36.01ng/L in the controls (p <0.001). Serum cTnI had a moderate negative correlation with ejection fraction (EF) in NIHF patients (R= -0.70, R2 = 0.492); and a positive correlation with left ventricular mass index (LVMI) (R= 0.12, R2 = 0.015). Mean cTnI levels increased with worsening grade of diastolic dysfunction in NIHF patients. Higher levels of serum cTnI was associated with worse New York Heart Association (NYHA) class of HF (p <0.001). Elevated serum cTnI level was associated with worsening clinical and echocardiographic indices of left ventricular function in NIHF patients suggesting that it is an important surrogate marker for worsening HF.